Privacy risk and the use of Facebook Apps: A gender-focused vulnerability assessment. Issue 96 (September 2020) - van der Schyff, Karl; Flowerday, Stephen; Furnell, Steven
Abstract: The surveillance and subsequent privacy risks (i.e., misuse of personal information) of Facebook App data constitute a persistent problem that affects millions of users. However, despite Facebook App research on specifics such as privacy concerns, value of information, and demographics, none of them has conducted vulnerability assessments on the use of Facebook Apps as influenced by specific factors such as age, gender, and information privacy attitudes. As such, the purpose of this study was to predict the extent to which these factors influence an individual's intention to continue using Facebook Apps as part of a gender-focused vulnerability assessment. We evaluate two hypotheses by way of ordinal logistic regression using data gathered from 621 respondents. The results are indicative of the following: First, females are particularly vulnerable to privacy risks as a function of continued use of Facebook Apps. More specifically, those risks related to Facebook's access to personal information. Second, results indicate that a user's age is nonsignificant in relation to the continued use of Facebook Apps. We conclude with several theoretical and practice-oriented information privacy recommendations.